Suicides in Siberia from 1925 to 1937: Causes, Dynamics, and Significance - T. I. Morozova (Научный диалог, 2024)
This article attempts to establish the causes, trace the dynamics, and assess the significance of suicides that occurred in the Siberian and West Siberian regions between 1925 and 1937. The research is based on a diverse array of sources, including statistical compilations, minutes from meetings, resolutions from party, Soviet, and Komsomol bodies, reports from special commissions, administrative correspondence, and materials from periodical publications. Through a comprehensive analysis of this heterogeneous information, the article demonstrates an increase in the number of suicides in Siberia, elucidates the demographic and social-professional composition of those who voluntarily ended their lives, and identifies the methods employed as well as the most common reasons for suicide. These parameters are analyzed in comparison with similar indicators across the RSFSR and the USSR, revealing the presence of regional specificity. The article challenges the prevailing historiographical view that placed sole responsibility for suicides on the individuals themselves. It presents evidence that one significant avenue for combating suicides involved holding accountable those whose actions or inactions contributed to these tragic events. The conclusion drawn is that, despite failing to achieve tangible success in preventing suicides, the higher political leadership at both regional and provincial levels managed to create an illusion that this phenomenon had been entirely eradicated.